(untitled) (Central Medical College Journal, 2023)
Background: Worldwide, myocardial infarction (MI) is an important cause of death. Number of AMI among young adult is increasing day by day in Bangladesh. Acute MI occurs most commonly at an older age. However, the incidence of acute MI in adolescents is increasing. This is partly due to an increase in cardiovascular risk factors (e.g. smoking, unhealthy diet), which might lead to premature atherosclerosis. However, several non-atherosclerotic causes of MI in adolescents are also described in the literature, such as vascular spasm due to the use of cocaine, amphetamine etc. We may assume that acute MI is not considered to be the most likely cause of chest pain in adolescents. Therefore, the risk of a dramatic outcome in this patient category may be significant. Myocardial infarction (MI) in the young (age < 45 years) is a significant problem; however, there is a scarcity of data on premature coronary heart disease and MI in the adolescent patients. MI in adolescents (age between 10–19 years) is extremely rare.Premature AMI, particularly in the setting of obstructive CAD and/or female sex, is an aggressive disease with high rates of recurrence and mortality, attributed largely to suboptimal control of modifiable risk factors.1 Collet et al2 reported that 1 in 3 patients with premature (≤45 years of age) CAD, of whom the majority experienced AMI, had at least 1 recurrent event over a follow-up period of 20 years. Strong independent predictors for recurrent events were persistent smoking, diabetes, hypertension. We present a case of the 17-year-old girl with extensive ST-segment elevated anterior wall myocardial infarction and found to have complete thrombotic occlusion of proximal left anterior descending coronary artery. Central Medical College Journal Vol 6 No 1 January 2022 Page: 49-53